Mass spectroscopy of picrotoxanolides of coriaria, coriamyrtin (1987)
Evidence for the identification and characterization of coriamyrtin, a toxic sesquiterpene lactone ocurring in Colombian material of Goriam microphylla. Poir., is provided by means of mass spectral data, discussions of the fragmentation patterns of the molecule and analogies with the related compound, tutin.